PROGRAM-TARGETED MANAGEMENT OF INNOVATIVE-INVESTMENT ACTIVITY OF LARGE COMPANIES - V. Busov (Вестник университета)
The necessity and efficiency of program-target management of innovative and investment activity of the companies are substantiated with the allocation of two interconnected subsystems-management of the company’s operation and development management integrated with the management systems of the processes of providing resources and service of all elements of the innovation process. The main organizational issues of building such a system is expounded. Special attention is paid to ensuring interaction of participants of programs of functioning and development through planning and operational and dispatching management of activity of the companies.